Navigating Religious Coexistence in Sri Lanka: Challenges, Reflections, and Implementation Prospects - Afra, Mohamed Razak Fathima; Abdullah, Mohamed Mahroof Ali (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2025)
Buddhism, Hinduism, Islam, and Christianity make up the complex religious mosaic that makes up Sri Lanka, and throughout its history, there has been peace and strife between different faiths. Through analyzing the data gathered from purposefully sampled interviews and secondary sources, this study explores the myriad issues that impair the harmonious coexistence of religions and provides viable solutions. The challenges include political interventions that exploit religion for electoral gain, the failure to implement constitutional and legal frameworks designed to promote ethnic harmony, the divisive influence of media, poor communication and coordination among stakeholders, an ineffective education system, and the lack of financial resources for meaningful projects. Reforms to education, interreligious dialogue, constitutional safeguards, regulating media, and legal actions are among the suggested remedies. The findings offer practical perceptions and actionable recommendations to enhance religious coexistence and support broader efforts toward peace and reconciliation in Sri Lanka.